ADOLESCENTS IN THE SCHOOL ENVIRONMENT AND KNOWLEDGE OF SEXUAL AND REPRODUCTIVE HEALTH - Ediane de Andrade Ferreira; Valdecyr Herdy Alves; Audrey Vidal Pereira; Diego Pereira Rodrigues; Eny Dórea Paiva; Inês Maria Meneses dos Santos (Universidade Federal do Paraná, 2018)
Objective: to analyze the knowledge of adolescents about sexual and reproductive health in the school environment. Method: qualitative exploratory descriptive study with 46 adolescents from three public schools of the state of Amapá, in the city of Macapá, from August to December 2016. Data was collected through interviews with the youngsters. The interviews were authorized by their parents or legal guardians and then transcribed and submitted to thematic content analysis. Results: Knowledge of the adolescents about sexuality associated with sexual intercourses, use of contraceptive methods, sex-related diseases and sexual orientation was analyzed. Conclusion: the various expres-sions of the adolescents revealed a direct relationship between sexual intercourse and the risks of unwanted pregnancy, and contamination by sexually transmitted infections and sexual orientation.